Spirometry in healthy and diseased. How it looks and how it should look like? - Wesołowski, Stefan (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Spirometry is most widely used pulmonary function test. Good quality of a test is essential for reliable assessment of lung function and interpretation of the results. Spirometry is usually performed in seated position, because of safety reasons. Age, height and weight, sex, and race must be recorded for calculating reference values. The forced exhalation maneuver to measure FVC and FEV1 has three phases: full inhalation, initial blast, and smooth completion of exhalation. Application of a nose clip is recommended. The ATS/ERS set specific criteria that must be met in order for the test to be considered valid. To be acceptable each trial must be without artifacts, has good start with extrapolated volume < 5% of FVC or 0.15 l whichever is greater, and good ending of exhalation, that is duration ł 6 s, or plateau in the volume-time curve. For an adequate test the subject should perform at least three acceptable maneuvers. The test is considered repeatable when difference between the largest and next largest FVC is Ł 0.15 l, and between the largest and next largest FEV1 is Ł 0.15 l. There are many different sources of error, including these related to equipment, human factors, both in subject and technician. Coaching by explanation, demonstrating the technique, and enthusiastic encouragement while patient performs the test are essential for obtaining good results. Poor patient effort and incomplete exhalation are the most common technical errors. Incomplete exhalation falsely reduce FVC and can mask obstruction by normalizing the FEV1/FVC ratio. Full inspiration is as important as full exhalation. Incomplete inspiration significantly affects the FVC obtained by determining the volume that can subsequently be exhaled. Slow inhalation or a pause at end inspiration can decrease PEF and FEV1.